Validity of competitive judo performance. Collective insights from the Japanese judo coaching community - Kinugasa, T.; Ishii, T. (The Arts and Sciences of Judo, 2021)
The sport of judo is one of combat sports originated in Japan and became an Olympic Games event for the first time in 1964 (Tokyo). Judo was founded by Dr. Jigoro Kano (1860-1938) and there have been rapid technological developments of modern judo with developments of science and art of coaching. However, evidence-based characteristics of competitive judo performance are not well documented. The aim of the study was to establish content validity of competitive judo performance by experts of the Japanese judo coaching community. The structure model of competitive judo performance was identified by literature review and constructed with 5 national coaches. The content validity of the structure model was confirmed by 21 judo experts with 98.0 ± 3.4% agreement after a two-round Delphi study. Three main characteristics in competitive judo performance were extracted: 1. fundamental movements e.g. etiquette (reiho), posture (shisei), moving forward, backward, or to sides (shintai); 2. interpersonal basic techniques - throwing techniques (nage-waza) and grappling techniques (katame-waza); and 3. interpersonal applied skills developed/shaped through the free sparring (randori) or competitions. It was also found that the development stages shifted from focusing on the fundamental movements, interpersonal basic techniques, and then interpersonal applied skills. The insights gained from this study provided a basis for improved understanding of competitive judo performance and it might be useful for judo coaches and other combat sports communities.